Cytauxzoon brasiliensis sp. nov. (Apicomplexa: Theileriidae), a new species infecting a little-spotted-cat (Leopardus tigrinus) (Carnivora: Felidae) from Brazil - Duarte, Matheus Almeida; de Oliveira, Camila Manoel; Honorato, Sandy Menezes; do Rosario Batista, Liliane Maria; Mendonça, Janaína Tavares; de Sousa, Davi Emanuel Ribeiro; Hirano, Liria Queiroz Luz; André, Marcos Rogério [UNESP]; de Castro, Márcio Botelho; Paludo, Giane Regina (Springer Nature, 2024)
Cytauxzoon spp. have been detected in Brazil infecting mainly asymptomatic domestic cats and wild felids. However, the supposed genetic similarity with the pathogenic Cytauxzoon felis is questionable because it is based on analysis of short sequences of the 18S rRNA gene. Herein, we describe a novel Cytauxzoon species infecting an asymptomatic little-spotted-cat (Leopardus tigrinus) based on morphological, histopathological, and molecular analyses. The animal was attended presenting a history of a run-over with multiple traumas. Although the little-spotted-cat was stabilized, he died a few days later. Ring-shaped merozoites within erythrocytes were found on blood smears and in the abdominal effusion. In addition, schizonts were observed in histiocytes in the liver. Phylogenetic analyses based on both near-complete 18S rRNA and cytb genes positioned the obtained sequences in a unique clade, albeit closely related to Cytauxzoon felis from the USA. Genetic divergences ranging from 0.004 and 0.067–0.068 were found between the near-complete 18S rRNA and cytb sequences of Cytauxzoon sp. detected in the little-spotted-cat and C. felis, respectively. This study evidenced the circulation of a novel Cytauxzoon species, herein named Cytauxzoon brasiliensissp. nov., in an asymptomatic wild felid species from Brazil. Further studies are necessary to identify Cytauxzoon species from domestic and wild felids in the country.